Corporate social responsibility, firm reputation, and firm performance: The role of ethical leadership - Zhu, Yan; Sun, Li-Yun; Leung, Alicia S. M. (Asia Pacific journal of management, 2014)
This study investigated the antecedents and outcomes of corporate social responsibility (CSR) and the moderating effects of ethical leadership. We collected two-wave, temporally lagged data from two sources (general and vice-general managers) in 199 tourism firms (hotels and travel agencies) in southeast China. We have two major findings. First, ethical leadership moderated its own indirect effect on firm reputation via CSR. It had an indirect and positive effect on firm reputation through CSR when ethical leadership was strong but not when it was weak. Second, ethical leadership also moderated the indirect effect of CSR on firm performance via firm reputation. There was an indirect and positive effect of CSR when ethical leadership was strong but not when ethical leadership was weak. This study highlights the role of ethical leadership in linking the antecedents and outcomes of CSR, and provides support for the stakeholder theory.